Registro fóssil de podocarpaceae na ilha Rei George e a sua relação com os eventos paleoclimáticos e paleoambientais - Fontes, Daiana (Universidade do Vale do Rio dos Sinos, 2008)
The composition and diversity of the Podocarpaceae representatives in the fossil plant assemblages of King George Island, north of Antarctic Peninsula, indicates their importance in that region during the Early Cenozoic, after a long evolutive history linked, since its origin, to the high southern latitudes. The fossil record attest an adaptability and capacity to conquer new areas that have no comparatives in other austral conifers, probably due to their seed dispersion by distinct groups of animals and the diverse forms and habits that their modern relatives still maintain. It guarantees their survival until today and their adaptation in nearly all latitudinal and altitudinal gradients. Seven distinct forms related to this family were described, characterized by two main kinds of leaf shoots. Those with scale and short leaf, bifacial flattened shoots are represented by two species of Lepidothamnus and by Halocarpus, Microcachrys and Dacrycarpus. The other one, with bilaterally flattened and big size leaves, with a sharp midrib, was associated with Saxegothaea and a species of Podocarpus, wich was for the first time described in the island taphofloras. The macrofossils are preserved by impressions and charcoalified materials, in the two main areas of the island where the lithologies are exposed in summer seasons, the Mount Wawel, at Admiralty Bay, and the Fossil Hill, at Fildes Peninsula. Represents what was included in two probably correlative lithostratigraphic units established in previous geological works, the Vièville Glacier and Fossil Hill formations. The fossil levels are composed mainly by volcanic grains, sometimes with signals of reworking by shallow lakes and deltas and confirm an environment and deposition linked to moments of active volcanism and inter-eruption phases. The comparisons with other fossil floras from the Antarctic Peninsula and Circum-Antarctic areas, and the radiometric ages indicates a probable lower mid-Eocene age, and wet and temperate climatic conditions, which deteriorates along the succession. The nearest modern relatives of the fossil taxa preserved in the taphofloras suggests also an unique, mixed and diversified vegetation, joining elements with distinct habits and that lives today in distinct altitudinal gradients, provides further evidence in support of the presence of high (volcanoes?) and coastal areas. The King George Island paleoflora flora also comprises a mixture of endemic, eastern Gondwana and South American elements, which reflect its position close to a major floristic boundary. At the same time confirms the microthermic conditions of climate in the north of Antarctic Peninsula at the Eocene times and the important role of the Gondwana drift apart, and the derivate climatic changes, in the modern disjunct distribution of the family.
Keywords: Paleogeography; Paleoclimate; Antarctic peninsula; King George Island; Eocene; Podocarpaceae; Paleobiogeografia; Paleoclima; Península Antártica; Ilha King George; ACCNPQ::Ciências Exatas e da Terra::Geologia